Comparação dos sintomas musculoesqueléticos e exposição postural da coluna vertebral entre trabalhadores de atividades sedentárias e dinâmicas - Minghini, Barbara Visciglia (2017)
Work-related musculoskeletal disorders (DORTs) depend on several risk factors for triggering them. Currently, they can be grouped into psychosocial, individual and occupational factors. Among the occupational factors, the biomechanical risks, especially the postures and movements adopted during the performance of the work activity may be associated to the development of DORTs. It is necessary to improve the knowledge about the occupational factors, deepening the postural exposure and its relation these disturbances. The objective of the present study was to compare these factors (individual, occupational, musculoskeletal symptoms, spinal incapacity, work stress, quality of life, postural exposure) in sedentary and dynamic workers. It is a cross-sectional and comparative field research. The convenience sample consists of workers divided into 2 groups: GS (group of workers with sedentary activities, n = 32) and GD (group of workers with dynamic activities, n = 36). To investigate musculoskeletal symptoms, spinal dysfunction, quality of life and stress were used: Nordic Osteomuscular Symptoms (NMS); Roland Morris (RM) of low back pain; WHOQOL-bref and "Job Stress Scale" (JSS). Logger Teknologi HB inclinometric sensors (INC) were used to assess the postural exposure of the spine at work. The Mann Whitney test was used for the comparison between the groups and the biserial point correlation to assess the correlation between musculoskeletal symptoms and posture. The groups presented similar similarity between age, GS (age 30.31 ± 9.59) and GD (33.86 ± 9.36), and anthropometric characteristics (height, weight and BMI) with no statistical difference (p> 0.05). For symptoms in the last 12 months, GD presented greater complaints in the lumbar regions (38.88%) and wrists and hands (36.11%). For GS, the regions most affected were neck (40.62%) and shoulders (37.5%). Despite complaints to the spine region, volunteers did not present functional disability when using Roland Morris. Regarding the QOL survey, the groups showed good scores for all domains (physical, psychological, social relations, environment) and similar results among them. Work stress in both groups was perceived with high demand, high control over work and low social support. The inclinometry data showed that GD presented higher angulations in all of the sensors evaluated with statistical difference, in the percentiles: 10 and 90 (head sensor), 10 and 90 (sensor C7 - T1), 90 (sensor T12 - L1) and In 90 (L5-S1). The angular velocity was 6 times higher for the dynamic group. There was a negative correlation between musculoskeletal symptoms and postural exposure to the neck in the GS suggesting that neutral posture protects against reported complaints. The opposite was found in the GD extreme postures suggested greater complaints in the neck and upper trunk